Review of the methodologies used in the assessment of root canal transportation (Mustansiria Dental Journal, 2025)
Background: The aim of this review is to identify, evaluate, and analyze the methodologies used for the quantitative assessment of root canal transportation. Numerous research papers have examined various transportation methods employed across different instrumentation approaches. A range of experimental models, utilizing simulated canals or extracted teeth provide valuable illustrations of the significance of root canal transportation. However, studies have utilized several approaches for quantitatively evaluating root canal movement, which poses challenges in comparing the results. In this study, a comprehensive literature review was conducted by searching databases such as PubMed, Google Scholar, and Scopus, as well as examining the reference lists of relevant papers. The search was carried out up to the year 2023, using relevant keywords to identify various methodologies employed in the evaluation of root canal transportation.Results: The methods used in the selected papers were gathered, evaluated, and categorized. Scientific studies typically follow a standardized structure that encompasses three fundamental stages: image capture, measurement of images, and computation of parameters.Conclusion:It is concluded that in future research concerning root canal transportation, a full evaluation of the root canal's length be performed using a 3D imaging technique is recommended. This method would necessitate measuring the distance from the center point for each segment, despite its inherent drawbacks of being laborious and expensive.